Validation of an inertial measurement unit to determine countermovement jump height - Toft Nielsen, E.; Jørgensen, P. B.; Mechlenburg, I.; Sorensen, H. (Asia-Pacific Journal of Sports Medicine, Arthroscopy, Rehabilitation and Technology, 2019)
Background: Vertical jump highs are used to quantify performance in the lower extremities. The aim of this study was to validate a wearable inertial measurement unit (IMU) for purpose of estimating countermovement jump height using the following methods: numerical double integration (NDI), takeoff velocity (TOV) and flight-time (FT). Methods: Fifteen students each performed three jumps in two different sessions, four weeks apart. Jump-heights calculated from motion capture and force plate were used as gold standard for global IMU position and center of mass (CoM) displacement, respectively. Results: The NDI method showed higher estimates for global position (1.39 cm, p = 0.025), and for CoM displacement (4.20 cm, p < 0.001). Narrow limits of agreements (LoA) were found (<4.8 cm). Further, a low tolerance level of determining equivalence (delta) between the two sessions regarding both global and CoM displacement (±2.80 and ± 2.90 cm) suggesting reasonable test-retest reliability.